A Comparative Study of the Photostabilization of Polyvinyl Chloride with Nano and Micro Nickel Oxide (Baghdad Science Journal, 2023)
NiO nanoparticle synthesis by chemical method and characterized by XRD with crystal size 11.72 nm and grain size 13 nm from FESEM image also NiO micro used ,two NiO as an additive to evaluate the possibility of producing photodegradable polymers, the practical application of solid-phase photocatalytic degradation of polyvinyl chloride (PVC- NiO composite films) was investigated. PVC has a negative impact on the environment since its polymer degrades slowly, yet it has a wide range of industrial applications and the amount used shows no evidence of diminishing use. Thus, a synthesis of modified PVC- NiO micro and nano has been studied with 0, 50, 100, 150, 200, 250, and 300 (hours) as irradiation time and a number of spectroscopic analyses such as FTIR and UV-VIS. Additionally, the effects of adding nanostructures to PVC chains on optical stability testing procedures were examined through indices (ICO, IPO, and IOH), weight loss measurements, UV and viscosity.